Protective effects of ADAM8 against cisplatin‐mediated apoptosis in non‐small‐cell lung cancer. (4th December 2012) - Zhang, Weifeng; Wan, Minghui; Ma, Lunchao; Liu, Xiang; He, Jianxing
Abstract A disintegrin, metalloproteinase 8 (ADAM8), is overexpressed in the vast majority of lung cancers and can be a diagnostic marker of lung cancer. We have investigated the effect of ADAM8 on the cisplatin resistance in non‐small‐cell lung cancer (NSCLC) cell lines. Stable cell lines overexpressing ADAM8 in A549 and H460 cells were generated, both of which have low endogenous ADAM8. Ectopic expression of ADAM8 rendered cells more resistant to cisplatin‐induced toxicity, increasing the half maximal inhibitory concentration (IC50) values by 1.85‐fold in A549 cells and 3.91‐fold in H460 cells relative to mock‐transfected cells. Moreover, silencing of ADAM8 in H647 cells with high endogenous level of ADAM8 sensitised them to cisplatin‐induced toxicity, with a lower IC50 value of 11.2 µM relative to an IC50 of 25.3 µM in mock‐transfected cells. Moreover, knockdown of ADAM8 caused a significant increase in cisplatin‐induced apoptosis assessed by annexin‐V/propidium iodide double staining, accompanying with enhanced cleavage of caspase‐3 and poly(ADP‐ribose) polymerase. Western blot analysis showed that a greater amount of phosphorylated signal transducer and activator of transcription 3 (STAT3) in ADAM8‐overexpressing A549 cells compared to parental or mock‐transfected cells. STAT3 silencing increased the susceptibility of ADAM8‐overexpressing A549 cells to cisplatin. Both Bcl‐2 and Mcl‐1 in ADAM8‐overexpressing A549 cells were profoundly diminished by STAT3 knockdown. Thus, ADAM8 is implicated in cisplatin resistance of NSCLC cells through activation of the STAT3 signalling pathway, and thus represents a potential therapeutic target in this malignancy.